Protestants, gender and the Arab renaissance in late Ottoman Syria - Womack, Deanna Ferree (Alternative histories., 2019)
The Ottoman Syrians - residents of modern Syria and Lebanon - formed the first Arabic-speaking Evangelical Church in the region. This book offers a fresh narrative of the encounters of this minority Protestant community with American missionaries, Eastern churches and Muslims at the height of the Nahda, from 1860 to 1915.